Micropropagation and Microrhizome Induction in Costus pictus D. Don Using In Vitro and Ex Vitro Nodal Segments as Explant - Kshetrimayum PUNYARANI (Notulae Scientia Biologicae, 2012)
Costus pictus D. Don is a potent anti-diabetic plant used in folk, ayurvedic and homeopathic system of medicine. Gene and protein expression of key targets in insulin signaling pathway have revealed that methyl tetracosonoate, a bio-active molecule from Costus pictus extract has anti-diabetic activity. The axillary buds of Costus pictus are dormant. The dormancy of axillary buds were broken when cultured in Murashige and Skoog (MS) medium supplemented with 3-4 ?M 6-benzylaminopurine (BAP) in combination with 0.2-1 ?M naphthalene acetic acid (NAA). The highest bud-break percentage was achieved in those supplemented with 0.6 ?M NAA and 3 ?M BAP. The sprouted axillary buds were transferred onto medium supplemented with 0.6 ?M NAA and 6-10 ?M BAP for shoot multiplication. The maximum average number of shoot was achieved in medium supplemented with 0.6 ?M NAA and 8 ?M BAP. The shoots were successfully rooted when transferred onto media supplemented with 1-12 ?M NAA or indole-3-acetic acid (IAA) and 3 ?M BAP. The maximum number of roots was found in 8 ?M NAA and 3 ?M BAP. The dormancy of in vitro axillary buds were also successfully broken in stems from which shoot apex were decapitated and cultured in MS medium with 0.6 ?M NAA, 7 ?M BAP and 5-13% sucrose. These sprouted in vitro axillary buds could be used as secondary explants for shoot multiplication. The maximum was in medium supplemented with 9% sucrose. Rhizomes were successfully induced when 4-month old plantlets were cultured on strength MS medium supplemented with 2.4 ?M NAA, 32 ?M BAP and 5-13% sucrose. Microrhizomes formed in 9% sucrose was largest in size with highest average fresh weight.